Subtype of atypia on cytology and risk of malignancy in pediatric thyroid nodules. Issue 5 (4th February 2022) - Cherella, Christine E.; Hollowell, Monica L.; Smith, Jessica R.; Zendejas, Benjamin; Modi, Biren P.; Cibas, Edmund S.; Wassner, Ari J.
Abstract : BACKGROUND: Thyroid nodules with atypia of undetermined significance (AUS) are challenging to manage because of their intermediate risk of malignancy. Subclassification of atypia can refine malignancy risk in adult AUS nodules but has not been evaluated in children. METHODS: This was a retrospective cohort study of pediatric patients (<19 years old) who underwent fine‐needle aspiration (FNA) of a thyroid nodule with resulting AUS cytology. Atypia was subclassified as nuclear only, architectural only, nuclear and architectural, or oncocytic. The primary outcome was the association between atypia subtype and malignancy. A secondary outcome was the association of atypia subtype with repeat FNA cytology. RESULTS: Sixty‐eight AUS nodules in 61 patients were analyzed. The median age at FNA was 16.2 years (range, 9.8‐18.9 years). Twenty‐four nodules (35%) were malignant. Nuclear atypia only was present in 17 nodules (25%), architectural atypia only was present in 27 nodules (40%), nuclear and architectural atypia was present in 20 nodules (29%), and predominantly oncocytic features were present in 4 nodules (6%). The presence of nuclear atypia was associated with a significantly increased rate of malignancy (22 of 37 [59%] vs 2 of 31 [6.5%]; P < .001), whereas architectural atypia was not associated with malignancy ( P = .8). Repeat FNA was performed in 42 of 68 nodules (62%). In nodules with initial nuclear and architectural atypia, benign repeat cytology had a high false‐negative rate (3 of 6; 50%). CONCLUSIONS: Pediatric AUS nodules with nuclear atypia have a high rate of malignancy, but architectural atypia is not associated with malignancy. In nodules with nuclear atypia, repeat FNA may inform clinical decisions regarding the need for resection. In the absence of suspicious clinical features, nodules without nuclear atypia might be considered for observation rather than resection or repeat FNA. Abstract : The subclassification of atypia on fine‐needle aspiration cytology is useful for guiding the management of pediatric thyroid nodules with atypia of undetermined significance. Nodules with nuclear atypia have a high risk of malignancy, whereas nodules with architectural atypia alone are unlikely to be malignant and may be considered for observation rather than resection.